Pantoea spp. Associated with Smooth Crabgrass (Digitaria ischaemum) Seed Inhibit Competitor Plant Species - Matthew T. Elmore; James F. White; Kathryn L. Kingsley; Katherine H. Diehl; Satish K. Verma (Microorganisms, 2019)
Digitaria ischaemum (Schreb.) Schreb. ex Muhl. and Poa annua L. are competitive, early successional species which are usually considered weeds in agricultural and turfgrass systems. Bacteria and fungi associated with D. ischaemum and P. annua seed may contribute to their competitiveness by antagonizing competitor forbs, and were studied in axenic culture. Pantoea spp. were the most common bacterial isolate of D. ischaemum seed, while Epicoccum and Curvularia spp. were common fungal isolates. A variety of species were collected from non-surface sterilized P. annua. Certain Pantoea spp. isolates were antagonistic to competitor forbs Taraxacum officinale, Trifolium repens. All bacterial isolates that affected T. officinale mortality were isolated from D. ischaemum seed while none of the P. annua isolates affected mortality. Two selected bacterial isolates identified as Pantoea ananatis were evaluated further on D. ischaemum, T. repens (a competitor forb) and P. annua (a competitor grass) alone and in combination with a Curvularia sp. fungus. These bacteria alone caused >65% T. repens seedling mortality but did not affect P. annua seedling mortality. These experiments demonstrate that Pantoea ananatis associated with D. ischaemum seeds is antagonistic to competitor forbs in axenic culture. The weedy character of D. ischaemum could at least in part stem from the possession of bacteria that are antagonistic to competitor species.